Choroidal Thickness in Patients with Mild Cognitive Impairment and Alzheimer's Type Dementia - Bulut, Mehmet (J Ophthalmol, 2016)
Aim. To asses both choroidal thickness differences among Alzheimer's type dementia (ATD) patients, mild cognitive impairment (MCI) patients, and healthy control (C) subjects and choroidal thickness relationships with cognitive performance. Methods. A total of 246 eyes of 123 people (41 ATD, 38 MCI, and 44 healthy C subjects) were included in this study. Complete ophthalmological and neurological examination was performed in all subjects. Choroidal thicknesses (CT) were measured at seven locations: the fovea, 500-1500-3000 μm temporal and 500-1500-3000 μm nasal to the fovea by enhanced depth imaging optical coherence tomography (EDI-OCT). Detailed neurological examination including mini mental state examination (MMSE) test which evaluates the cognitive function was applied to all participants. Results. The ages and genders of all participants were similar in all groups. Compared with healthy C subjects, the CT measurements at all regions were significantly thinner both in patients with ATD and in patients with MCI than in healthy C subjects (p < 0.05). The MMSE scores were significantly different among ATD patients, MCI patients, and healthy C subjects. They were 19.3 ± 1.8, 24.8 ± 0.9, and 27.6 ± 1.2 in ATD, MCI, and healthy controls, respectively (p < 0.001). There were also significant correlation between MMSE score and choroidal thickness at each location (p < 0.05). Conclusions. CT was reduced in ATD patients and MCI patients. Since vascular structures were affected in ATD patients and MCI patients, they had thin CT. Besides CT was correlated with degree of cognitive impairment. Therefore CT may be a new biomarker in diagnosis and follow-up of MCI and ATD patients.